GAMBARAN PERILAKU CUCI TANGAN DAN PENGGUNAAN APD PERAWAT TENTANG RISIKO PENYEBARAN INFEKSI NASOKOMIAL - Sari, Ceria Permata; Maulana, Muhammad Ali; Fauzan, Suhaimi; Mita, Mita; Neri, Ervina Lili; Wahyarti, Heni (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
Abstract Background: Hospital is one of the health services demanded according to standards by the community. But hospitals also have a high risk of infection, both due to treatment and medication. Of the many health workers, nurses are one who plays a role in the quality of service. In improving quality, nurses' behavior needs to be considered as a form of hospital prevention against infection. Measures that can prevent infection by washing hands and using PPE properly. Objective: Knowing the description of hand washing behavior and the use of nurses' personal protective equipment about the risk of spreading nasocomial infections. Method: Descriptive research using quantitative descriptive methods with total sampling techniques and using univariate test analysis. The subjects of this study were 67 respondents. Data collection was carried out by observation method regarding hand washing behavior and the use of nurses' personal protective equipment in hospitals.Results: The results of the study of 59 respondents studied found that 30 nurses behaved obediently (50.8%) while nurses who did not comply with the moment of hand washing amounted to 29 people (49.2%). With respondents who had a handwashing step behavior adhering to six steps amounted to 31 people (52.5%), while nurses who did not comply with six steps of hand washing amounted to 28 people (47.5%). While respondents who had compliant behavior in the use of PPE amounted to 34 people (57.6%), while nurses who did not comply in the use of PPE amounted to 25 people (42.4%). Conclusion: Inpatient nurses in hospitals have the majority of behaviors that comply with hand washing and the use of PPE (personal protective equipment) Keyword: Personal Protective Equipment; Hand Washing; Nasocomial Infection; Behavior Abstrak Latar Belakang : Pelayanan kesehatan yang diberikan oleh rumah sakit harus mematuhi standar yang diharapkan oleh Masyarakat.. Namun fasilitas kesehatan tersebut juga memiliki resiko tinggi terhadap infeksi, baik karena perawatan maupun pengobatan. Dari banyaknya petugas kesehatan, perawat ialah salah satu yang berperan dalam mutu pelayanan. Dalam meningkatkan mutu, perilaku perawat perlu diperhatikan sebagai bentuk dari pencegahan rumah sakit terhadap infeksi. Tindakan yang dapat mencegah terjadinya infeksi dengan cuci tangan serta penggunaan APD dengan benar. Tujuan : Mengetahui Gambaran Perilaku Cuci Tangan dan Penggunaan Alat pelindung diri Perawat Tentang Risiko Penyebaran Infeksi Nasokomial. Metode : Studi deskriptif dilakukan dengan metode deskriptif kuantitatif, teknik total sampling, serta analisis uji univariat pada 67 responden. Pengambilan data dilakukan dengan metode observasi mengenai perilaku cuci tangan dan penggunaan Alat pelindung diri perawat di Rumah sakit.Hasil : Hasil penelitian dari 59 responden yang diteliti didapatkan 30 orang perawat berperilaku patuh (50.8%) sedangkan perawat yang tidak patuh terhadap momen cuci tangan berjumlah 29 orang (49.2%). Dengan responden yang memiliki perilaku langkah cuci tangan patuh terhadap enam langkah berjumlah 31 orang (52.5%), sedangkan perawat yang tidak patuh terhadap enam langkah cuci tangan berjumlah 28 orang (47.5%). Sedangkan responden yang memiliki perilaku patuh dalam penggunaan APD berjumlah 34 orang (57.6%), sedangkan perawat yang tidak patuh dalam penggunaan APD berjumlah 25 orang (42.4%). Kesimpulan : Perawat rawat inap yang ada di Rumah Sakit memiliki perilaku mayoritas patuh terhadap cuci tangan maupun penggunaan APD (alat pelindung diri) Kata kunci: Alat Pelindung Diri; Cuci Tangan;Infeksi Nasokomial;Perilaku;